Advancing alternatives analysis: The role of predictive toxicology in selecting safer chemical products and processes. (21st May 2017) - Malloy, Timothy; Zaunbrecher, Virginia; Beryt, Elizabeth; Judson, Richard; Tice, Raymond; Allard, Patrick; Blake, Ann; Cote, Ila; Godwin, Hilary; Heine, Lauren; Kerzic, Patrick; Kostal, Jakub; et al.
ABSTRACT: Alternatives analysis (AA) is a method used in regulation and product design to identify, assess, and evaluate the safety and viability of potential substitutes for hazardous chemicals. It requires toxicological data for the existing chemical and potential alternatives. Predictive toxicology uses in silico and in vitro approaches, computational models, and other tools to expedite toxicological data generation in a more cost‐effective manner than traditional approaches. The present article briefly reviews the challenges associated with using predictive toxicology in regulatory AA, then presents 4 recommendations for its advancement. It recommends using case studies to advance the integration of predictive toxicology into AA, adopting a stepwise process to employing predictive toxicology in AA beginning with prioritization of chemicals of concern, leveraging existing resources to advance the integration of predictive toxicology into the practice of AA, and supporting transdisciplinary efforts. The further incorporation of predictive toxicology into AA would advance the ability of companies and regulators to select alternatives to harmful ingredients, and potentially increase the use of predictive toxicology in regulation more broadly. Integr Environ Assess Manag 2017;13:915–925. © 2017 SETAC Key Points: In chemical regulation, alternatives analysis (AA), also known as "alternatives assessment, " is a rapidly advancing method used to determine the relative safety and viability of potential alternatives to existing products or processes that use hazardous chemicals. The problem of data gaps is exacerbated in the AA context in which multiple chemicals contained in various alternatives must be characterized and compared. Predictive toxicological methods offer the potential for obtaining the necessary toxicity and exposure estimates in substantially less time and at significantly less cost than convention methods. Four steps will speed integrating predictive toxicology and AA: 1) Use case studies to advance the integration, 2) use predictive toxicology for screening chemicals of concern in the short term, 3) use existing resources to the fullest, and 4) support trans‐sector and transdisciplinary activities.